Integrated Nutrient Management on Biomass, Oil Yields and Essential Oil Composition of Peppermint (Mentha piperita L.) and Residual Fertility in a Hilly Soil. Issue 3 (2nd April 2016) - Verma, Rajesh Kumar; Verma, Ram Swaroop; Rahman, Laiq-Ur; Kalra, Alok; Patra, Dharani Dhar
Abstract: A field experiment was conducted to study the influence of combined use of farm yard manure and inorganic fertilizers on biomass and essential oil yields, chemical and microbial biomass carbon and nitrogen of soil grown with peppermint ( Mentha piperita ) in a hilly region, Bageshwar, India. Combined application of both farm yard manure and inorganic fertilizers increased the biomass and oil yields of peppermint compared to sole inorganic fertilizers treatments. The treatments receiving both farm yard manure and inorganic fertilizers improved the soil organic carbon and total N from initial value of 3.9 to 7.0 g kg -1 soil and 0.27 to 0.58 g kg -1 soil, respectively. A significant improvement has been noticed in soil respiration, soil microbial biomass carbon and nitrogen compared to inorganic fertilizer alone. Moreover, different proportions of inorganic fertilizers with farm yard manure had significant variation on available major soil nutrients. A significant correlation coefficient (r= 0.41* to 0.98**) was observed between yields and soil properties. The quality of essential oil was good and acceptable for the market.